2012
DOI: 10.1080/13691058.2012.671960
|View full text |Cite
|
Sign up to set email alerts
|

Boyfriends and injecting: the role of intimate male partners in the life of women who inject drugs in Central Java

Abstract: The international literature shows that HIV-risk behaviour for women mostly occurs in the context of intimate relationships. Power imbalances in the social, economic and cultural spheres put women at risk. This paper addresses the roles of male partners in women's engagement in drug-use behaviour and drug-related HIV-risk behaviour in Indonesia. Data were gathered through in-depth interviews with 19 women who had injected drugs in the previous month in three sites in central Java. Most of the women had male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…The majority of FWID inject with their main partners and engage in unsafe injection behaviors with their partners. This supports other literature on injection drug use in intimate relationships which has found that FWID share drug equipment and engage in risky injections with their male partners (El-Bassel et al, 2013; Lazuardi et al, 2012; Seear et al, 2012; Simmons et al, 2012; Wagner et al, 2013). The most common unsafe behaviors were (1) drawing a drug solution from a vessel shared with others and (2) preparing drugs with another person and then splitting the solution.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The majority of FWID inject with their main partners and engage in unsafe injection behaviors with their partners. This supports other literature on injection drug use in intimate relationships which has found that FWID share drug equipment and engage in risky injections with their male partners (El-Bassel et al, 2013; Lazuardi et al, 2012; Seear et al, 2012; Simmons et al, 2012; Wagner et al, 2013). The most common unsafe behaviors were (1) drawing a drug solution from a vessel shared with others and (2) preparing drugs with another person and then splitting the solution.…”
Section: Resultssupporting
confidence: 90%
“…Using the same syringes and drug equipment after their partners raises the female partner’s risk for HIV and HCV infection (Lazuardi et al, 2012; Wagner, Jackson Bloom, Hathazi, Sanders, & Lankenau, 2013). However, by refusing to share syringes or drug equipment FWID may increase their risk of physical and sexual intimate partner violence (IPV) (El-Bassel et al, 2011; 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Friends (41, 44, 47, 48, 50, 51, 55, 56, 60, 68, 70, 73, 77), family (41, 43, 44, 51, 52, 55, 68, 7073), intimate partners (42, 48, 49, 52, 57, 59, 60, 64, 68, 7072, 77), acquaintances (37, 43, 77), gang members (63), elders (65) and drug dealers (41, 42) were all described as influential. Different types of social interactions shaped injection initiation.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the vulnerabilities described above and, in particular, stigma and discrimination, FWID may access health services at later stages of deteriorating health. These issues are further complicated by the fact that FWID face greater challenges than MWID in obtaining sterile injection equipment and accessing harm reduction programmes (Des Jarlais, Feelemyer, Modi, Arasteh, & Hagan, 2012), due to a reliance on intimate partners to provide drug-using resources including needles (Lazuardi et al, 2012) and greater levels of discrimination experienced when seeking HIV and drug use treatment as well as a lack of female-specific services (El-Bassel et al, 2010, 2014a. Each of these factors may play a role in the gender disparities in mortality rates found in the Mravcik et al (2014) study.…”
Section: Females Who Inject Drugs and Non-idu Female Sex Partners Of mentioning
confidence: 98%